2005
DOI: 10.4028/www.scientific.net/msf.475-479.655
|View full text |Cite
|
Sign up to set email alerts
|

New Phases in a Multicomponent High Ruthenium Single Crystal Superalloy

Abstract: Three unusual Ru-rich phases have been identified in a multicomponent Ni-base single crystal superalloy, including a L21 Ru2AlTa Heusler phase, a B2 RuAl phase and a hcp Re(Ru)-rich δ phase. These phases have their own preferential precipitation location within the dendritic structure. No conventional topologically-close-packed (TCP) phases have been observed with thermal exposure at 950oC for 1500 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, in a multicomponent system such as the superalloys studied here, it is believed that a twophase field would exist, [34] as schematically shown in Figure 11. Precipitation of b-RuAl rather than the Heusler phase [25,32] in the SRZ of the F-13 was most likely linked to the emergence of the Ni-denuded IDZ during the coating formation. The compositional shift achieved due to the loss of Ni led to the precipitation of b-RuAl in the IDZ.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, in a multicomponent system such as the superalloys studied here, it is believed that a twophase field would exist, [34] as schematically shown in Figure 11. Precipitation of b-RuAl rather than the Heusler phase [25,32] in the SRZ of the F-13 was most likely linked to the emergence of the Ni-denuded IDZ during the coating formation. The compositional shift achieved due to the loss of Ni led to the precipitation of b-RuAl in the IDZ.…”
Section: Discussionmentioning
confidence: 95%
“…The microstructural aspects and creep behavior of most of the experimental Ru alloys examined in the present study, namely, F-16, F-18, F-20, F-22, and F-30, have been previously reported. [20,21,32,35] It has been shown that the alloy F-30 exhibits a good microstructural stability and has the best creep properties among all the alloys mentioned. [21,35] For example, the minimum creep rate for the F-30 alloy at 950°C/290 MPa is approximately 10 -10 s -1 , while it is approximately an order of magnitude higher for the remaining alloys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co can substitute Ni in the crystal lattice, and it is broadly deemed one of the main elements in γ′-strengthened Ni-based superalloys. Based on previous works, it was found that Co can cause γ′-Ni 3 (Al,Ti) to transform into γ′-(Ni,Co) 3 (Al,Ti) [ 12 , 13 , 14 ], reduce the stacking fault energy, and modify the lattice mismatch of γ/γ′ to influence the morphology of γ′ precipitates [ 15 , 16 ]. However, the effects of Co on other precipitates, such as carbides and the σ phase, have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%